ACHIVEMENT ANALYSIS BEFORE AND DURING CORONA VIRUS PANDEMIC OF PROPERTY AND REAL ESTATE COMPANIES - Hastuti, Rini Tri; Setiyono, Stefani Velisia (Graduate Program of Universitas Tarumanagara, 2025)
The Corona Virus Pandemic pandemic has a systemic effect on all sectors, especially in the business sector. This effect has resulted in the collapse of business pillars in several sectors, but has also resulted in extraordinary growth in several other sectors. This pandemic has disrupted the global economy and has had an effect on property and real estate companies. The effect of this pandemic is very significant, and property and real estate around the world are forced to face major challenges in maintaining their financial Achivement. Every corporate certainly has a goal to generate max profit. If the corporate can achieve this goal, then the corporate will be considered to have good corporate Achivement and quality. To assess the quality of the corporate can be seen from its financial achivement. This experiment was conducted with the aim of testing and analyzing differences in the financial Achivement of property and real estate companies before and during the Corona Virus Pandemic pandemic. The time of this experiment was from 2018-2019 before Corona Virus Pandemic and 2020-2021 during Corona Virus Pandemic. The sample selection for this experiment used purposive sampling and the experiment design used was descriptive experiment. The samples used in this experiment were 120 samples from 10 companies. The data was processed with Paired Sample t-Test using Microsoft Excel and SPSS 26, the data was taken from the annual financial reports of property and real estate companies. The proxies used are liquidity with Cash Ratio, profitability with Return on Assets and solvency with Debt to Assets Ratio. This experiment shows that there are differences in the Achivement of Cash Ratio and Return on Assets in the period before and during Corona Virus Pandemic. The Debt to Assets Ratio shows that there is no difference in the corporate's financial Achivement in the period before and during Corona Virus Pandemic. The implication of this study is to provide implications that the property and real estate must improve its corporate Achivement with the resources it has effectively and minimize all risks during the Corona Virus Pandemic pandemic, so that the corporate's profitability improves and recovers quickly from the effect of the Corona Virus Pandemic.